EVALUASI PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) DI KOTA PEKANBARU TAHUN ANGGARAN 2014-2015 - Gustian Putradi AD; Muhammad Adnan; Kushandajani Kushandajani (Journal of Politic and Government Studies, 2015)
Jaminan Kesehatan Nasional (JKN) program is the policy of Indonesian Government to fulfil the basic needs of Indonesian public. JKN program began implemented for the first time on 1st of January in 2014 in all regions in Indonesia , including the city of Pekanbaru , Riau Province. JKN's program is the new program from government that still needs more suggestions and improvements so that it can be maximal in use. It takes the evaluation and monitoring of JKN program so that the program can run well.The purpose of this research is to evaluate the Jaminan Kesehatan Nasional Program in Pekanbaru period 2014-2015. Beside that, this research will explain the impact of aspect of implementation, consequence, and effectiveness from Jaminan Kesehatan Nasional (JKN) Program in Pekanbaru. The research method that used is descriptive quantitative. The main source of this research is taken by sharing some of kuisoners to the certain respondents and the secondary data that taken from the archives and documents that relate with the research. The analysis technical is using descriptive statistic analysis by presenting the datas that has collected into tables, graphics, and diagrams.From the result of the research could be known that the implementation process of JKN's program in pekanbaru is performed very well generally. Which became a little note is needs a little improvement in terms of payment of dues per month by the participants JKN , because the results of the research mentioned that the participants JKN still lacking discipline in paying dues per month. In the consequence aspect program, the hospital has helped the government to do JKN's program and made it success in Pekanbaru. In the aspect of the effectiveness impact program , averagely JKN participants had been satisfied and feel helped by the program JKN of government.Improving the services to the public  is the suggestion that could be given to BPJS Kesehatan Pekanbaru as the organizer of the JKN program in Pekanbaru so that the program of JKN can run better. The hospitals which being the partner of BPJS Kesehatan should doing the health services well to JKN participant. Hopefully the public become proactive to looking for the information and understand about Jaminan Kesehatan Nasional program.Keywords  : Jaminan Kesehatan Nasional (JKN) program, Pekanbaru